Identifikasi dan Efektivitas Berbagai Teknik Pengendalian Hama Baru Ulat Grayak Spodoptera frugiperda J. E. Smith pada Tanaman Jagung berbasis PHT- Biointensif - Rizki Darmawan Septian; Lutfi Afifah; Tatang Surjana; Nurcahyo Widyodaru Saputro; Ultach Enri (Jurnal Ilmu Pertanian Indonesia, 2021)
The presence of new pest Spodoptera frugperda J. E. Smith has the potential to reduce corn production, so its existence needs to be controlled. The aim of this research is to obtain control techniques that could reduce the intensity of S. frugiperda pest’s attack. The research was conducted from June to October 2020. The experiment was designed in a randomized block design (RBD) with 9 replications and 3 treatments consisting of non-control (NP), PHT-biointensive (BI), and synthetic pesticides. In BI treatment, neem leaf extract (25 mL/plot) and Beauveria bassiana (6,25 g/plot) were used. Meanwhile, the PS treatment used deltametrin active ingredient (3,125 mL/plot). The volume of spray used was 1,25 L. The results showed that PS control techniques gave the best results in suppressing the intensity of fall armyworm S. frugiperda attacks (0,57%-7,04%) followed by BI treatment (0%-6,89%) and NP (0,97%-8,29%). The highest pest populations overall were found in NP treatment and the lowest in PS treatment. PS treatment provided the highest production result with a cob weight of 18,6 kg/plot (24,81 tons/ha), while BI treatment of 17,00 kg/plot (22,72 tons/ha) and NP of 15,44 kg/plot (20,64 tons/ha). The results of the correlation test between the intensity of pest attacks and production results showed that the higher the pest attack, the lower the harvest weight produced. Therefore, pest control by using synthetic pesticides made from active deltametrin is declared effective in suppressing the intensity of attacks and populations of fall armyworm S. frugiperda and able to provide high production results. Keywords: corn, intensity of attack, Spodoptera frugiperda